2021
DOI: 10.3389/fimmu.2021.796855
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Rich Lipid Rafts as Platforms for SARS-CoV-2 Entry

Abstract: Since its appearance, the Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2), the causal agent of Coronavirus Disease 2019 (COVID-19), represents a global problem for human health that involves the host lipid homeostasis. Regarding, lipid rafts are functional membrane microdomains with highly and tightly packed lipid molecules. These regions enriched in sphingolipids and cholesterol recruit and concentrate several receptors and molecules involved in pathogen recognition and cellular signaling. Choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 220 publications
1
72
0
Order By: Relevance
“…Although mature CTSL protein is present in podocytes, Calu-3 and glomerular endothelia cells, pro-CTSL is present in all the cell types which may explain the presence of the CTSL mRNA in all the cell types even when they do not express mature CTSL protein. It has been suggested that SARS-CoV-2 entry into host cells depends on the presence of cholesterol-rich lipid rafts, which facilitates membrane fusion through proteases such as TMPRSS2 or endosomal pathway using Cathepsin B&L ( Palacios-Rápalo et al, 2021 ). Our results suggests low levels of TMPRSS2 expression in podocyte, and we speculate that the use of BSG/CD147 as a receptor and CTSL as a processing enzyme for viral entry mediated by S protein might be a preferred mechanism for the podocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Although mature CTSL protein is present in podocytes, Calu-3 and glomerular endothelia cells, pro-CTSL is present in all the cell types which may explain the presence of the CTSL mRNA in all the cell types even when they do not express mature CTSL protein. It has been suggested that SARS-CoV-2 entry into host cells depends on the presence of cholesterol-rich lipid rafts, which facilitates membrane fusion through proteases such as TMPRSS2 or endosomal pathway using Cathepsin B&L ( Palacios-Rápalo et al, 2021 ). Our results suggests low levels of TMPRSS2 expression in podocyte, and we speculate that the use of BSG/CD147 as a receptor and CTSL as a processing enzyme for viral entry mediated by S protein might be a preferred mechanism for the podocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, other raft-resident lipids such as sphingolipids and ceramides were seen as important in the mechanisms of fusion and virus entry into the cell, highlighting the importance of the integrity of lipid rafts in these mechanisms (42). In this context, the pharmacological redistribution of cholesterol and impaired lipid raft formation hampers the SARS-CoV-2 SARS-CoV-2 entry, and consequently the virus replication (34,(43)(44)(45). In line with the results obtained here with simvastatin pretreatment, other drugs that affect not only the synthesis but also the traffic of cholesterol through the endosomal pathway, such as itraconazole, fluoxetine and amitriptyline showed promising results as adjuvant therapy for COVID-19 (42,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the caveolar/lipid raft and cytoskeleton system may involve or assist in the entry process of SARS-CoV-2 pseudovirus. Lipid rafts enriched in sphingolipids and cholesterol are functional membrane microdomains, which provide a platform to allow receptors such as ACE2, CD147, and TMPRSS2 to be recruited for binding to the viral spike protein [ 31–34 ]. A cytoskeleton is composed of three major types of cytoskeletal polymers including actin filaments, microtubules, and intermediate filaments [ 35 ].…”
Section: Discussionmentioning
confidence: 99%